Hyaluronic Acid and Its Derivatives in Coating and Delivery Systems: Applications in Tissue Engineering, Regenerative Medicine and Immunomodulation. Issue 22 (6th October 2016) - Knopf‐Marques, Helena; Pravda, Martin; Wolfova, Lucie; Velebny, Vladimir; Schaaf, Pierre; Vrana, Nihal Engin; Lavalle, Philippe
Abstract : As an Extracellular Matrix (ECM) component, Hyaluronic acid (HA) plays a multi‐faceted role in cell migration, proliferation and differentiation at micro level and system level events such as tissue water homeostasis. Among its biological functions, it is known to interact with cytokines and contribute to their retention in ECM microenvironment. In addition to its biological functions, it has advantageous physical properties which result in the industrial endeavors in the synthesis and extraction of HA for variety of applications ranging from medical to cosmetic. Recently, HA and its derivatives have been the focus of active research for applications in biomedical device coatings, drug delivery systems and in the form of scaffolds or cell‐laden hydrogels for tissue engineering. A specific reason for the increase in use of HA based structures is their immunomodulatory and regeneration inducing capacities. In this context, this article reviews recent literature on modulation of the implantable biomaterial microenvironment by systems based on HA and its derivatives, particularly hydrogels and microscale coatings that are able to deliver cytokines in order to reduce the adverse immune reactions and promote tissue healing. Abstract : This review covers recent literature about how the modulation of the biomaterial microenvironment can be achieved by systems based on hyaluronic acid and its derivatives such as hydrogels and coatings that are able to deliver cytokines with the aim of reducing the adverse immune reactions and promote tissue healing.